FUNGSI PENGAWASAN CAMAT UNTUK MENINGKATKAN EFISIENSI DAN EFEKTIFITAS KERJA PEGAWAI DI KECAMATAN KAWANGKOAN KABUPATEN MINAHASA - Mewengkang, Norma (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract:sub district head as the head of the unit of work in a sub district supervisory functions as the roles to improveeffectiveness and efficiency of the work of employees concerning the services that come into contact with thecommunity. The purpose of this research is to know the description of the function of supervision of the subdistrict head to increase the efficiency and effectiveness of work of employees in the sub district KawangkoanMinahasa regencyThis research uses Qualitative Descriptive method where data retrieval in field or object of research datacollected by researchers in person with the intention of directly spaciousness. The determination of samplerespondents conducted in purposive sampling where writers/researchers specify or choose deliberatelyagainst the sample of respondents that add up to 17 peopleThe supervisory function of the sub district head in the improvement of work productivity in the Governmentapparatus sub district Kawangkoan views efficiency and effectiveness is already well underway. This isapparent in the management control through the Organization, in the implementation of policies, proceduresand job duties. Several other factors that have not been fullest including mental attitude is still lacking but ifany deficiencies there may be clear in the implementation of the duties and responsibilities of the employeeswill be the maximum so that it will have an effect on the success of the tasks performed, both in the areas ofgovernance, development, community, and other administrative tasks.Keywords: supervision, efficiency, effectiveness